Radical surgery for gallbladder carcinoma. Long-term results. - Shirai, Y (1992)
The authors' objective was to evaluate the effectiveness of radical surgery with lymph node dissection for gallbladder carcinoma. Long-term results were analyzed in 40 patients in a 5-year study. The authors divided the 40 cases into two groups: 20 without positive nodes and 20 with positive nodes. In the group without positive nodes, one patient who underwent R1 resection died of a recurrence at 1 year 7 months. Seventeen of the 19 patients treated with R0 resection survived more than 5 years. The 5-year survival rate was 85% (17/20). In the group with positive nodes, 9 of the 13 patients treated with R0 resection survived more than 5 years, whereas the seven patients treated with R1 or R2 resection died within 5 years. The 5-year survival rate was 45% (9/20). Patients treated by R0 resection showed a 5-year survival rate of 69% (9/13). Thus we documented the favorable long-term results of radical surgery. R0 resection is a prerequisite for long-term survival. The results justify radical surgery with lymph node dissection.